Genetic diversity, heritability, and productivity of new sugarcane (Saccharum officinarum L.) clones on paddy fields for enhanced sugar production in Indonesia - Arofatuz Zumroh; Setyo Budi; Wiharyanti Nur Lailiyah (Jurnal Ilmiah Pertanian, 2023)
Sugar production in Indonesia has decreased by 2.12 million tons (4.65%) in 2020 due to the limited supply of superior varieties. The purpose of this study was to understand the potential of the expected superior clones before being released as new superior varieties. This study was conducted in Sidoarjo, Indonesia which has alluvial soil types. This study used a randomized block design (RBD) with one treatment factor (clone) consisting of clones SB01, SB03, SB04, SB11, SB12, SB19, SB20, and varieties PS 881, and MOJO. Data analysis used 5% ANOVA, 5% least significance difference test, correlation test, genetic diversity test, and heritability test. The results of the analysis showed significant differences with all treatments at 48, 50, and 52 weeks after planting (WAP) in the variable brix while the sugarcane stems weight, rock crystal, and yield were significantly different only at 52 WAP which were tested in multilocation in paddy fields and alluvial soil types. Clone SB01 showed the highest brix value of 26.88%, the highest stem weight of 149.20 tons/ha, the highest yield of 10.63%, rock crystal 15.87 tons/ha, the value of genetic diversity in the moderate category was seen in crystal characters (12.55 %), phenotypic diversity in the moderate category was seen in crystal characters (14.364%) and the heritability value was in the fairly high category in brix characters (0.96%). This study shows that the characters inherited from their parents are relatively stable.